2008
DOI: 10.3892/ijo.32.3.603
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor effect of pegylated interferon in the rat hepatocarcinogenesis model

Abstract: Abstract. Interferon (IFN) is a multifunctional cytokine which works as a suppressor of hepatocarcinogenesis. Pegylated interferon (PEG-IFN) is a modified form of IFN with different pharmacokinetics. We evaluated the antitumor effect of PEG-IFN using a rat hepatocarcinogenesis model. Male Fisher Rats were treated using the Solt and Faber model to induce liver cancer. IFN and PEG-IFN were administered from chemical initiation, and pre-neoplastic foci and neoplastic hepatocellular carcinoma (HCC) were examined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Several reports have shown the inhibitory effects of IFN therapy on the development of HCC. In these reports, the inhibitory effect was considered to be the result of the remission of inflammation, necrosis, and fibrosis in addition to the direct action of IFN on tumor cells [35][36][37][38][39]. Recently, several studies were conducted to show the effect of IFN therapy after curative treatment of HCC, which reduced the risk for recurrence and improved the rate of survival.…”
Section: Discussionmentioning
confidence: 94%
“…Several reports have shown the inhibitory effects of IFN therapy on the development of HCC. In these reports, the inhibitory effect was considered to be the result of the remission of inflammation, necrosis, and fibrosis in addition to the direct action of IFN on tumor cells [35][36][37][38][39]. Recently, several studies were conducted to show the effect of IFN therapy after curative treatment of HCC, which reduced the risk for recurrence and improved the rate of survival.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies reported that AFP might enhance tumor cell growth and the proliferation of human hepatoma, and that IFN therapy, irrespective of viral eradication, reduced this risk. [ 30 33 ] Thus, non-SVR patients might have a reduced risk of HCC after IFN treatment due to their lower AFP levels. Therefore, the combined use of post-treatment AFP level and FIB4 index may provide a more precise prediction of the risk of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, investigations from other teams come up with different results. A study shows that activation of Notch1 in the pre-neoplastic foci might be associated with the progression of HCC in the diethylnitrosamine-induced hepatocarcinogenesis model (31). Downregulation of Notch1 signaling by a Notch1 inhibitor curcumin, inhibits tumor growth in human HCC (32).…”
Section: Discussionmentioning
confidence: 99%